2023
DOI: 10.3390/ani13192998
|View full text |Cite
|
Sign up to set email alerts
|

African Swine Fever: The State of the Art in Italy

Silvia Pavone,
Carmen Iscaro,
Annalisa Dettori
et al.

Abstract: African swine fever (ASF) is a severe viral disease of domestic pigs and Eurasian wild boars (Sus scrofa) caused by the African swine fever virus (ASFV). ASF is endemic in sub-Saharan Africa, where 24 genotypes of the virus have been reported. Between the late 1950s and the early 1980s, genotype I ASFV emerged in Europe, including Italy. In June 2007, a second ASF epidemic wave caused by genotype II was registered, involving several European and extra-European countries, including Italy in 2022. The present pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The active search for wild boar carcasses (carcass types A or C) requires the involvement of several people and huge economic resources [ 42 , 43 , 44 ]. The results of this study confirmed the key role of actively searching for and removing carcasses and eradicating ASF in combination with hunting activities [ 45 ] and the importance of implementing, even over the long term, user-friendly apps for efficient data collection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The active search for wild boar carcasses (carcass types A or C) requires the involvement of several people and huge economic resources [ 42 , 43 , 44 ]. The results of this study confirmed the key role of actively searching for and removing carcasses and eradicating ASF in combination with hunting activities [ 45 ] and the importance of implementing, even over the long term, user-friendly apps for efficient data collection.…”
Section: Discussionmentioning
confidence: 99%
“…Hunters, a special and often overlooked group of citizen scientists [ 39 ], offer unique advantages given their knowledge of the territory, facilitating the collection of long-term data over large areas that otherwise could not be possible to investigate [ 40 ]. Thus, researchers and hunters should be considered a standard partnership [ 44 ]. Hunters play an important role in wildlife management and, thus, also in the implementation of disease control measures in the wild boar population, especially in the enforcement of ASF control measures and passive disease surveillance [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This structurally complex virus [ 25 ] causes severe hemorrhagic disease in domestic pigs [ 27 , 28 ]. Being a significant global veterinary concern [ 26 , 29 , 30 , 31 , 32 ], primarily due to the lack of effective vaccine and vaccine prototypes [ 33 ], it is particularly worrying in large countries such as China in which the pig industry is a strong economic supporter [ 34 , 35 ]. Secondly, a mouse model was employed to assess the safety and immunogenicity of secretory granules based on the green fluorescent protein (GFP).…”
Section: Introductionmentioning
confidence: 99%
“…Up to October 2023, genotype II was responsible for 1063 cases in wild boar and 16 outbreaks in domestic pigs (ADNS, as of 2 October 2023). The Italian epidemic spread is currently characterized by long-distance jump transmission from infected regions (i.e., Liguria and Piedmont) to previously ASF-free areas, such as Lazio, Lombardia, Campania, Calabria, and Sardinia [ 28 , 29 , 30 ]. Transmission via the human factor was confirmed in mainland Italy [ 29 ].…”
Section: Introductionmentioning
confidence: 99%